ANALYSIS OF PRODUCTION CAPACITY PLANNING AND CONTROL IN PT. KRAKATAU WAJATAMA WITH ROUGHT CUT CAPACITY PLANNING (RCCP) - Irawan, Irawan; Nasiatin, Titin; Adha, Suhroji; Julyanto, Octoberry; Rani, Citra Puspita; Dimas P.K, Rahardian (AGUSPATI Research Institute, 2020)
Production planning and control is an absolute must for companies that produce goods or services. This is considered very important because it is the core of the entire production process. Every company may not carry out a production activity if it does not conduct production planning and control activities. Production plan at PT. Krakatau Wajatama on capacity planning and production of profile steel products requires a production plan based on demand that might come so that it needs an appropriate plan so that there is no overproduction. Therefore, integration between production plans and capacity plans needs to be done in order to obtain a realistic production plan. The method used is forecasting, capacity planning using RCCP can be done with the conversion process of the Production Plan or MPS based on order requests in bales in the period January 2019 to December 2019 into the time requirement of the production machine. Estimated results of 2019 demand for profile steel production are IWF-Flange, U-Chanal, L-Angels. In January 2019 it was 250836,713 minutes, February 2019 was 225731.5425 minutes, March 2019, and for IWF-Flange, U-Chanal, L-Angels products. In January 2019 it was 298080 minutes, February 2019 was 259200 minutes, March 2019 was 298080 minutes. company capacity planning needs on profile steel products namely IWF-Flange, U-Chanal, L-Angels using machine capacity that is used multiplied by hours per shift at times of shifts per day multiplied by workdays per period by converting production plans or MPS into capacity by using the RCCP concept with the Capacity Planning Using Overall Factors (CPOF) method.